Practical current control techniques for torque ripple minimization in SR motors - Gobbi, R.; Ramar, K. (2008)
The switched reluctance motor (SRM) has many benefits owing to its low cost, simple and rugged construction, and comparatively high torque-to-mass ratio. Because of the saturation effect and the variation of magnetic reluctance with respect to rotor position, all the relevant characteristics of the machine are highly nonlinear functions of both rotor position and phase current. The ultimate outcome of all these nonlinearities is that the generated torque contains significant ripples. The nonlinearities in SRM have been extensively studied and many control strategies to reduce the generated torque ripples have been proposed in the literatures. However, the problem of reduction of generated torque ripple still remains an active area of research especially for low speed applications. A new method called fuzzy iterative approach (FIA) is introduced in this work to modulate the phase current profile. FIA uses a multiplying factor in the conventional current calculation method, and a fuzzy rule base determines this multiplying factor by a heuristic judgment iteratively to reduce the torque ripple to zero. The modulated phase current for zero torque ripples is stored in a look-up table, which is utilized for practical implementation. Experimental verification under closed-loop speed control with the stored reference current data has been done. Various current control techniques to track the reference current closely to minimize the torque ripple are investigated and explained in this paper. The experimental results indicate that the torque ripple is reduced to lie within 5% of the desired steady torque.